1959
DOI: 10.4141/cjas59-015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strain and Sex on the Relationship of Protein to Energy in the Rations of Growing and Finishing Bacon Pigs

Abstract: Rations varying in energy (65 to 79 per cent TDN or 69 to 88 per cent apparent digestible energy) and protein (13 to 21 per cent) were studied in two experiments with 120 pigs of four strains. Rate of liveweight gain tended to be fastest in pigs fed high energy-high protein rations throughout. Males gained more rapidly than females, with strain differences being evident. Strain × sex interactions in rate of gain were present in both the growing and finishing period, with a ration × strain interaction present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

1965
1965
1972
1972

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 7 publications
(1 reference statement)
7
21
0
Order By: Relevance
“…However, there was still a need for an anatomical study in swine which would encompass not only normal patterns of tissue growth but also the direct influence of outside factors on these patterns. CANADTAN Cuthbertson and Pomeroy (1.962) in swine, Berg (1968) and Berg and Butterfield (1968) (Bowland and Berg, 1959;Braude et al, 1963;Brooks et al, L964;Buck, 1963;Cuthbertson and Pomeroy,1962;McCampbell and Baird, 1961; Wagnet et aI., (1963). By 91 kg liveweight, pigs had 84Vo of-the muscle and 66Vo of the fat that was present at 1'I4 kg liveweight.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was still a need for an anatomical study in swine which would encompass not only normal patterns of tissue growth but also the direct influence of outside factors on these patterns. CANADTAN Cuthbertson and Pomeroy (1.962) in swine, Berg (1968) and Berg and Butterfield (1968) (Bowland and Berg, 1959;Braude et al, 1963;Brooks et al, L964;Buck, 1963;Cuthbertson and Pomeroy,1962;McCampbell and Baird, 1961; Wagnet et aI., (1963). By 91 kg liveweight, pigs had 84Vo of-the muscle and 66Vo of the fat that was present at 1'I4 kg liveweight.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that an increase in lean content of pork carcasses has been achieved by feeding higher levels of prorein (1,2,6,'g, 10). Consequently, some suppliers of swine feeds have' recommended a'single highprotein rltiol to be fed through growing and finishing srages.…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study were to evaluate the efiect of levels of dietary protein and sex on performance and carcass traits, and possible g.notyp'" (99x) b1r environmeni (level of protein) interaction (2) found that gilts required less feed per pound of gain, but had a smaller average daily gain than bairows during the finishing period; this apparent contradiction, compared with our findiigs, in growtt and feed efficiency may be partially explained bv the strain by sex interaction observed in their experiment but not in ours.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are inherent problems common to all species and some refer to the methods of experimentation and the parameters used to measure efficiency in the pig. In the first category are factors such as the changing requirements during growth (Braude, 1958) the effect of genotype (Bowland & Berg, 1959) the endocrine status of the animal (Prescott, 1963) and the sex (Robinson & Lewis, 1964) as well as considerations such as the non-availability of amino acids. Problems associated with the method of experimentation have only recently been recognized.…”
Section: Radio-chromium Sesquioxide As An Intestinal Marker In Sheep mentioning
confidence: 99%